Normothermic machine perfusion (NMP) inhibits proinflammatory responses in the liver and promotes regeneration - Jassem, W; Xystrakis, E; Ghnewa, Y; Yuksel, M; Pop, O; Martinez-Llordella, M; Jabri, Y; Huang, X; Lozano, J; Quaglia, A; Sanchez-Fueyo, A; Coussios, C; et al. (Wiley, 2018)
Background and Aims Liver transplantation is a successful treatment for patients with liver failure. However, organ shortage results in over 11% of patients losing their chance of a transplant due to liver decompensation and death. Ischemia/reperfusion injury (IRI) following conventional cold storage (CS) is a major cause of injury leading to graft loss after liver transplantation. A novel method of organ preservation, normothermic machine perfusion (NMP), provides oxygen and nutrition during preservation and allows aerobic metabolism. NMP has recently been shown to enable improved organ utilization and post‐transplant outcomes following a Phase I and a Phase III randomized trial. The aim of the present study is to assess the impact of NMP on reducing IRI and to define the underlying mechanisms. Methods We transplanted and compared 12 NMP with 27 CS‐preserved livers by performing gene microarray, immunoprofiling of hepatic lymphocytes and immunochemistry staining of liver tissues for assessing necrosis, platelet deposition and neutrophil infiltration, and the status of steatosis after NMP or CS pre‐ and post‐reperfusion. Results Recipients receiving NMP grafts showed significantly lower peak AST levels than those receiving CS grafts. NMP altered gene‐expression profiles of liver tissue from pro‐inflammation to pro‐healing and regeneration. NMP also reduced the number of IFN‐γ and IL‐17 producing T cells and enlarged the CD4posCD25highCD127negFOXP3pos Treg pool. NMP liver tissues showed less necrosis and apoptosis in the parenchyma and fewer neutrophil infiltration compared to CS liver tissues. Conclusion Reduced IRI in NMP recipients was the consequence of the combination of inhibiting inflammation and promoting graft regeneration.